Teaching about Oppression and Rebellion: The "Peasants Are Revolting" Game. Issue 2 (11th April 2021) - Asal, Victor; Willis, Charmaine; Linebarger, Christopher; Jahanbani, Nakissa
ABSTRACT: Jean Jacques Rousseau wrote that "Man is born free, but is everywhere in chains." Whereas the former claim of the quote is contestable and gendered, the latter part is empirically true from slavery to economic exploitation and widespread oppression that occurs to this day. Nevertheless, history shows that rarely will people take up weapons and rebel against the powerful. We have found that students often do not understand why this should be the case, given the rights that all people deserve. We use the Peasant Game exercise in class to shine a light on why most people, most of the time, endure repression and choose not to rebel. The game is played in turns with some students as lords, who decide how "food" will be apportioned, and other students as peasants, who produce the food. We discuss how power differentials occur and the difference they make. Students who play the game come away with a better understanding of why many people decide not to fight back against oppression—even if it is the right thing to do.